Workplace Injustice: Catalyzing Organizational Change for African American women in Academia - Abbie Salcedo; Jeremy Bohonos (Adult Education Research Conference, 2022)
Following George Floyd's death, few studies have examined the effectiveness of Diversity and Inclusion programs. This article will examine the impact of racial workplace injustice among African American women faculty.
Keywords: DEI; Higher Education; Racial Workplace Injustice; African American Women; Women in the Professoriate